Nigeria - Lagos State : States Finances Review and Agenda for Action - World Bank (Washington, DC, 2012)
This study on Nigeria Lagos State, states finances review and agenda for action reviews Lagos State's fiscal performance in recent years, highlight the main risks that may affect the fiscal outlook in the medium term, and help the Lagos State Government (LASG) develop an agenda for deepening the reforms in key aspects of public finance management (PFM) and service delivery, based on further analytical work. The quality of information has unfortunately been a constraint in this study. It affected the ability of the study team to make relevant observations and policy recommendations, in particular on the expenditure side. The data limitation also suggests that the first priorities for the government in PFM reform should be extending the coverage of the budget, improving the classification system, and reporting revenues and expenditures accurately and transparently.